POLYSEMY TYPES AND LEVELS OF FRENCH LINGUISTIC TERMS (based on the material of the French language) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-63-74The lexical analysis of scientific terms in the works of French-speaking linguists (from F. de Saussure to modern researchers) allows identifying the epistemological reasons for the development of semantics and the formation of polysemy of terminological units. The semantic features of the considered terms determine a new classification of polysemy types depending on the level of terminological abstraction.Key words: scientific language, terminology, linguistic term, polysemy, monosemy, homonymy